Setting Up Representative Offices in China - Devonshire-Ellis, Chris; Scott, Andy; Woollard, Sam (China Briefing, The Practical Application of China Business, 2011)
Do you want to do business in China? If you are already in this vast country and want to know more, or if you have never tried your hand at this fascinating market, then this book is for you. This Guide is a practical overview for the international businessman to understand the rules, regulations and management issues regarding establishing Representative Offices in China. We will help you to understand the implications of what can initially appear be a complicated and contradictory subject. This book tells you the basics of what you need to know, and point you at the structures you should use as well as some of the pitfalls. This book is the first in a new series of books on doing business in China, which will progressively cover such topics as setting up wholly foreign-owned enterprises, setting up joint ventures, tax, IP and many other vital issues for foreign investors in this exciting market.